2007
DOI: 10.1073/pnas.0704774104
|View full text |Cite
|
Sign up to set email alerts
|

Dominant-negative DISC1 transgenic mice display schizophrenia-associated phenotypes detected by measures translatable to humans

Abstract: Here, we report generation and characterization of Disrupted-InSchizophrenia-1 (DISC1) genetically engineered mice as a potential model for major mental illnesses, such as schizophrenia. DISC1 is a promising genetic risk factor for major mental illnesses. In this transgenic model, a dominant-negative form of DISC1 (DN-DISC1) is expressed under the ␣CaMKII promoter. In vivo MRI of the DN-DISC1 mice detected enlarged lateral ventricles particularly on the left side, suggesting a link to the asymmetrical change i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
358
3
2

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 397 publications
(378 citation statements)
references
References 44 publications
15
358
3
2
Order By: Relevance
“…It may be necessary to explore the utility of temporal or spatial genetic knockdowns to gain information about the importance of a number of genes in schizophrenia. Recent work with DISC1 confirms the value of this approach (Hikida et al, 2007;Pletnikov et al, 2007).…”
Section: Animal Preparations and Their Use In Schizophrenia Drug Discmentioning
confidence: 79%
See 1 more Smart Citation
“…It may be necessary to explore the utility of temporal or spatial genetic knockdowns to gain information about the importance of a number of genes in schizophrenia. Recent work with DISC1 confirms the value of this approach (Hikida et al, 2007;Pletnikov et al, 2007).…”
Section: Animal Preparations and Their Use In Schizophrenia Drug Discmentioning
confidence: 79%
“…This said, several of the models may prove useful for generating an increased understanding of the pathophysiology of schizophrenia. Arguably, the most informative genetic models appear to be the calcineurin conditional knockout mouse, the neuregulin hypomorphic mouse, and the recently described DISC1 mutant mouse (Stefansson et al, 2002;Miyakawa et al, 2003;Hikida et al, 2007). There are two drawbacks to the currently available genetic models that must be mentioned.…”
Section: Animal Preparations and Their Use In Schizophrenia Drug Discmentioning
confidence: 99%
“…Although both groups identified increased lateral ventricle size in the absence of any change in total brain volume, Hikida et al 52 detected this abnormality only at 6 weeks of age and demonstrated, rather surprisingly, that by 3 months (when the transgene is no longer expressed) there is no detectable difference in lateral ventricle size between wildtype and transgenic animals. Pletnikov et al, 53 however, detected the increased lateral ventricle size in adult mice.…”
Section: The Phenotype Of Mouse Disc1 Variantsmentioning
confidence: 97%
“…Studies in the maternal infection model, the DISC1 model, and prenatal exposure to methylazoxymethanol acetate (MAM), have shown that alterations of brain development during specific periods of pre or postnatal development produce discrete disruptions that lead to behavioral and neurochemical effects that include a decreased number of PVinterneurons (Hikida et al, 2007;Lodge and Grace, 2007;Meyer et al, 2007;Lodge et al, 2009). In the MAM model, where the mitotoxin is applied during interneuronal proliferation/migration stage, the number of PV-interneurons decreased in specific brain regions that correlated with alterations in oscillatory activity and decreased lateral inhibition in adulthood (Lodge et al, 2009).…”
Section: Neurodevelopmental Origins Of Schizophrenia: Activation Of Tmentioning
confidence: 99%